2009
DOI: 10.1386/ijis.22.2.125/1
|View full text |Cite
|
Sign up to set email alerts
|

Contradictions in the (still) gendered structure of Portuguese newspapers' production and discourse

Abstract: This article discusses the access of women to Portuguese newspapers against the background of a more general debate over the role of the media in the (re)production of gender inequalities in western societies. On one hand, we stress the qualitative and quantitative developments of women's participation as journalists in newspapers, by comparing the results of previous investigation in the Portuguese context with the statistics of our own research and with the statistics provided by the last Global Media Monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Having employed van Leeuwen"s (1996[2006]) visual social semiotics, either solely or in conjunction with other frameworks, researchers have shown how different visual factors manipulate meaning in the visual texts of different magazines, newspapers and advertisements (e.g., Bell & Milic, 2002;Bohlke, 2006;Borhart, 2003;Godeo, 2009;Lin & Ihara, 2009;MartínezLirola, 2009MartínezLirola, , 2010Manolache, 2010;Oyama, 2007;Pinto-Coelho & Mota-Ribeiro, 2009). However, to the best of the researchers' knowledge, very few studies have examined gender representation in the images of ELT materials (e.g., Kordjazi, 2012) and textbooks (e.g., Tahririan & Sadri, 2013) based on Kress and van Leeuwen"s (2006) visual social semiotics.…”
Section: Social Semioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having employed van Leeuwen"s (1996[2006]) visual social semiotics, either solely or in conjunction with other frameworks, researchers have shown how different visual factors manipulate meaning in the visual texts of different magazines, newspapers and advertisements (e.g., Bell & Milic, 2002;Bohlke, 2006;Borhart, 2003;Godeo, 2009;Lin & Ihara, 2009;MartínezLirola, 2009MartínezLirola, , 2010Manolache, 2010;Oyama, 2007;Pinto-Coelho & Mota-Ribeiro, 2009). However, to the best of the researchers' knowledge, very few studies have examined gender representation in the images of ELT materials (e.g., Kordjazi, 2012) and textbooks (e.g., Tahririan & Sadri, 2013) based on Kress and van Leeuwen"s (2006) visual social semiotics.…”
Section: Social Semioticsmentioning
confidence: 99%
“…However, Borhart (2003) found that images of female athletes on magazine covers showed them as being powerful. Further research on newspapers, however, has shown that women have been less present in images than in the linguistic text and although they have been linguistically depicted as active in hard sections like political and public life, and civic responsibilities, they have been visually found in conceptual representations and in soft sections such as culture, art, and entertainment (Pinto-Coelho & Mota-Ribeiro, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Entre otros motivos, Lavie & Lehman-Wilzig (2005) sostienen que la imprecisión heurística de este objeto de estudio se debe, principalmente, a falta de uniformidad de las herramientas de investigación que se han empleado (mayoritariamente encuestas y entrevistas en profundidad a periodistas hombres y mujeres, así como el análisis de contenido de su producción periodística). Existe, además, una línea de investigación que combina dos supuestos, aparentemente contradictorios: que la feminización de las noticias depende de la mayor o menor presencia de las mujeres en las redacciones (Djerf-Pierre & Löfgren-Nilsson, 2004;Ross & Carter, 2011;Chambers & al., 2004;Armstrong, 2004;Pinto-Coelho & Mota-Ribeiro, 2009); y que el «estilo femenino» no es sino un efecto colateral de los cambios que ha experimentado el periodismo durante las últimas décadas, al margen de la discriminación o de las desigualdades sociodemográficas (De-Bruin, 2000a;van-Zoonen, 1998).…”
Section: Introductionunclassified